ZAKAT UNTUK PEMBANGUNAN MASJID - Zainuddin Zainuddin (JURIS (Jurnal Ilmiah Syariah), 2017)
This article presents an overview of Islamic Law on the properties of zakat used for the construction of mosques. This study uses literature research, because the study of Islamic law will seek answers through literature, both in the form of legal propositions and opinions of the scholars. From the results of this study found the answer that there are two opinions of scholars about the law of building a mosque with zakat property. The first opinion allows and the second opinion does not allow. While the author more tends to the opinion that does not allow, because zakat is the right of people (ashnaf) while the construction of the mosque can be obtained fromwakaf ummah.